Automatic airway analysis on multidetector computed tomography in cystic fibrosis: correlation with pulmonary function testing - Wielpütz, Mark Oliver; Eichinger, Monika; Weinheimer, Oliver; Ley, Sebastian; Mall, Marcus A.; Wiebel, Matthias; Bischoff, Arved; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Puderbach, Michael (Journal of thoracic imaging, 2013)
Purpose: To evaluate the fully automatic quantification of airway dimensions on chest multidetector computed tomography (MDCT) performed in cystic fibrosis (CF) patients. Airflow indices including predicted forced expiratory volume in 1 second (FEV1%) were used to study the impact on regional lung function. - Materials and Methods: MDCT data of patients with CF (14 children and 23 adults) and of control patients (11 children and 22 adults) were used to compute total diameter (TD), lumen area (LA), and wall thickness (WT) using dedicated software. Pulmonary function testing including FEV1% was performed in parallel and correlated with MDCT parameters in a generation-based analysis. - Results: TD was largely increased in CF patients (third-generation to fourth-generation airways in children, first to ninth in adults; P<0.05). LA remained unchanged, but WT was also larger in CF compared with controls (third generation to sixth generation in children, first to eleventh in adults; P<0.05). In adult CF patients significant negative correlations for TD, LA, and WT with FEV1% were found for intermediate airways (fifth to seventh generation; r=−0.7 to −0.9) but not in pediatric CF patients and controls. - Conclusions: Automatic airway analysis succeeded in quantifying specific pathologies such as airway dilatation and wall thickening in CF patients at different ages. Moreover, our results indicate a shift in main airflow resistance to intermediate airways in cases of chronic CF. The objective computational parameters TD, LA, and WT should be considered for assessment and follow-up of CF airway disease.
Gesehen am 08.11.2021